Approaches to optimize therapeutic bacteriophage and bacteriophage-derived products to combat bacterial infections - Reuter, Monika; Kruger, Detlev H. (Virus genes, 2020)
The emerging occurrence of antibiotic-resistant bacterial pathogens leads to a recollection of bacteriophage as antimicrobial therapeutics. This article presents a short overview of the clinical phage application including their use in military medicine and discusses the genotypic and phenotypic properties of a potential “ideal” therapeutic phage. We describe current efforts to engineer phage for their improved usability in pathogen treatment. In addition, phage can be applied for pathogen detection, selective drug delivery, vaccine development, or food and surface decontamination. Instead of viable phage, (engineered) phage-derived enzymes, such as polysaccharide depolymerases or peptidoglycan-degrading enzymes, are considered as promising therapeutic candidates. Finally, we briefly summarize the use of phage for the detection and treatment of “Category A priority pathogens”.